(untitled) (Global Journal of Management and Business Research, 2019)
This study identified long-run and short-run relationship as well as causal direction of medium and high tech (MHT) trade (proxy for tech-intensive trade), economic growth and CO2 emissions in BRICS for the period of 1992-2015 applying ARDL bound test approach and error-correction based Granger causality. The disequilibrium (non-stationary) characteristics of CO2 emissions in China during 1992-2014, along with unavailability of MHT trade data prior to 1992, constrained the analysis of short-run and longrun relationship among the variables for the country. The study found that structural change did not affect CO2 emissions in India and Russia in the long-run but it did in the short-run in India. The study did not find any long-run cointegration among the variables for South Africa. It identified long-run causality running from MHT trade and growth to CO2 emissions for India and Russia, whereas long-run causality directed from MHT trade and CO2 emissions to growth was found in Brazil and India, and causality running from CO2 emissions and growth to MHT trade only held for India.